Effects of acoustic nonlinearities on the ultrasonic backscatter coefficient estimation - Coila, Andres (2019)
The backscatter coefficient (BSC) is a fundamental property of tissues and can be used to classify tissues. Two BSC calibration methods are the planar reflector method and the reference phantom method. In both methods, linear acoustic propagation is assumed. In this study, the calibration methods were evaluated when acoustic nonlinear distortion was present. Radio frequency data were acquired from two physical phantoms using a 5 MHz single-element transducer and low power (one excitation level) and high power (six increasing excitation levels) excitation signals. BSCs estimated from the high power settings were compared to the BSCs estimated using the low power by calculating the root mean square error (RMSE). The BSCs were parameterized by fitting the BSC curve to a power law and estimating the power law exponent and by estimating the effective scatterer diameter (ESD). When using the planar reflector method, estimates of the exponent were observed to monotonically increase in value versus increasing excitation level and the ESD decreased with increasing excitation level. The RMSE increased monotonically versus excitation level using the planar reflector method but did not increase using the reference phantom method. The results suggest that the effects of nonlinear distortion are minimized using the reference phantom method. (C) 2019 Acoustical Society of America.